IDENTIFIKASI POTENSI DAN PEMANFAATAN LIMBAH PERTANIAN DI KABUPATEN BEKASI - Rahmanto, Muhammad Ikhwan (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2011)
Crops and livestock produce harvest and also waste. Potential of agricultural and livestock waste in the district of Bekasi is quite large. Potential should have the feasibility to be utilized. Some commodity source of waste consisting of seven commodities, namely paddy, corn, bananas, sheep, layer, broilers, and beef cattle. Utilization of agricultural and livestock waste need to consider the application of efficiency technology, in order to be applied by local farmers. In addition to the utilization of waste need to prioritize the needs of farmers, namely the utilization of waste for organic fertilizer and animal feed.